Factor influence service quality at hotel in Kuala Terengganu /Caroline Anak Francis & Ireine Anak Steward Maurice - Francis, Caroline; Steward Maurice, Ireine (Faculty of Hotel and Tourism, 2018)
Hotel industry and tourism contributes to the economic development of the state of Terengganu. The industry is challenged with various obstacles and problems in the terms of fulfilling the prospect of their guests through the delivery of high quality services. Quality service delivery allows and ensures that the guests who are staying at the hotel become loyal customers to the hotel. This study is to examine factor of service quality that influence customer satisfaction in selected resorts and hotels in Kuala Terengganu. The study applies secondary data obtained from various websites from the internet related to these hotels. Based on the review have been made, we do review both negative and positive comments. The results indicate that the highest variable that influence customers satisfied with the hotel is rooms